The effect of strain rate and temperature on the hysteresis of shear dampers of LY225 low-yield-strength steel. (15th April 2022) - Qu, Zhe; Kishiki, Shoichi; Sakata, Hiroyasu
Highlights: Dynamic cyclic loading test on full-scale shear dampers of low-yield-strength steel; Significant combined effect of strain rate and temperature on hysteresis behavior of dampers; A one-dimensional rheological model was proposed and calibrated for dynamic effects. Abstract: In a passive-controlled structure for seismic protection, energy dissipating devices such as steel dampers are supposed to concentrate earthquake energy dissipation and to sustain strain amplitudes and strain rates much larger than those in primary structural elements. The self-heating and the moderate strain rate in the order of magnitude of 1 s −1 may have non-negligible effects on the hysteresis behavior of dampers. To investigate this combined effect, eleven full-scale shear dampers of LY225 steel were subjected to either dynamic or quasistatic cyclic loading at shear strain amplitudes of 2.00–10.0 %. The comparison between the dynamic and quasistatic hysteresis curves shows that the strain-rate effect alone increased the shear strength of the dampers by 8.0–11.6 %, while the elevated temperature due to self-heating significantly accelerated the decrease in the shear strength of the dampers during dynamic loading. A one-dimensional rheological model is proposed and calibrated based on the test results to simulate the strain-rate and temperature dependencies of steel dampers. It offers a promising tool for improved simulation of the seismic response of steel dampers in nonlinear response history analyses.